2005
DOI: 10.1080/02844310500300362
|View full text |Cite
|
Sign up to set email alerts
|

Construction of pigmented skin equivalent and its application to the study of congenital disorders of pigmentation

Abstract: We have constructed a pigmented skin equivalent and used it to study the hyperpigmentation seen in café-au-lait macules to elucidate whether the pigmented skin equivalent could be used as a model of congenital hyperpigmentary disorders. When we used fibroblasts derived from café-au-lait macules of neurofibromatosis type 1, the amount of pigment was significantly greater than in models using cells derived from normal skin. Quantities of pigment were not seen when keratinocytes derived from solitary café-au-lait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Addressing this concern requires the use of validated disease models that exhibit high specificity and sensitivity; are noninvasive, reproducible and accessible; and can reliably distinguish between stages or subtypes of disease. Several in vitro models for studying human skin pigmentation have been devised, [21][22][23] but these fall short in replicating the dynamics of in vivo skin.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing this concern requires the use of validated disease models that exhibit high specificity and sensitivity; are noninvasive, reproducible and accessible; and can reliably distinguish between stages or subtypes of disease. Several in vitro models for studying human skin pigmentation have been devised, [21][22][23] but these fall short in replicating the dynamics of in vivo skin.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the use of melanocytes has to be taken into consideration not only in skin grafts for clinical applications but also for the modulation of melanogenesis by pro‐pigmenting or de‐pigmenting agents (Cario‐André et al., 2006; Régnier et al., 1999). The use of pigmented skin equivalents has also been adopted to obtain a better understanding of congenital hyperpigmentary disorders (Okazaki et al., 2005).…”
Section: Addressing Skin Model Limitationsmentioning
confidence: 99%
“…2 The pathogenesis of PIH/PIE is yet to be fully elucidated. [3][4][5] In 2016, Isedeh et al developed and validated an in vivo model for PIH using 35% trichloroacetic acid (TCA) and found that TCA-induced PIH has similar clinical, spectroscopic and histological properties to acne-induced PIH. 1 This year, the same group who developed the first in vivo model for PIH improved the previous study design by incorporating a dose-response design and molecular techniques to further explore the mechanism of PIH and PIE.…”
Section: Postinflammatory Hyperpigmentation and Erythema: New Insight...mentioning
confidence: 99%